2021
DOI: 10.1093/cvr/cvab187
|View full text |Cite
|
Sign up to set email alerts
|

Different cardiovascular and pulmonary phenotypes for single- and double-knock-out mice deficient in BMP9 and BMP10

Abstract: Aims BMP9 and BMP10 mutations were recently identified in patients with pulmonary arterial hypertension (PAH), but their specific roles in the pathogenesis of the disease are still unclear. We aimed to study the roles of BMP9 and BMP10 in cardiovascular homeostasis and pulmonary hypertension using transgenic mouse models deficient in Bmp9 and/or Bmp10. Methods and Results Single- and double-knockout mice for Bmp9 (constitutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 56 publications
3
35
0
Order By: Relevance
“…In our hands, the global KD of Bmp10 in adult Bmp9-KO mice leads to a phenotype that is partially in accordance with this work, characterized by vessel dilation, a decrease in blood pressure, and a larger heart. 108 Together these results indicate that blockade of Bmp10 at postnatal stage in Bmp9-KO mice leads to the death of these pups while loss of Bmp10 in adult Bmp9-KO mice is viable although these mice present many vascular problems. It is also interesting to note, that BMP10 ANF mice crossed with Bmp9-KO mice, which will lead to a rapid loss of BMP10 after birth as BMP10 is mainly expressed by the right atria at this stage, leads to viable mice underscoring a role for other sources of BMP10 (such as the liver) at postnatal stage.…”
Section: Loss Of Both Bmp9 and Bmp10mentioning
confidence: 74%
See 3 more Smart Citations
“…In our hands, the global KD of Bmp10 in adult Bmp9-KO mice leads to a phenotype that is partially in accordance with this work, characterized by vessel dilation, a decrease in blood pressure, and a larger heart. 108 Together these results indicate that blockade of Bmp10 at postnatal stage in Bmp9-KO mice leads to the death of these pups while loss of Bmp10 in adult Bmp9-KO mice is viable although these mice present many vascular problems. It is also interesting to note, that BMP10 ANF mice crossed with Bmp9-KO mice, which will lead to a rapid loss of BMP10 after birth as BMP10 is mainly expressed by the right atria at this stage, leads to viable mice underscoring a role for other sources of BMP10 (such as the liver) at postnatal stage.…”
Section: Loss Of Both Bmp9 and Bmp10mentioning
confidence: 74%
“…It was shown that adult Bmp10 knockdown in the C57BL/6 background was not lethal and showed no obvious vascular phenotype. 107,108 More recently, a mouse model specifically deleted for Bmp10 in the right atrium was generated (Bmp10 ANF ). 109 These mice overcame embryonic cardiac lethality and were viable with no obvious phenotype, suggesting that cardiac BMP10 is not involved in postnatal vascular remodeling.…”
Section: Loss Of Bmp10mentioning
confidence: 99%
See 2 more Smart Citations
“…The main effector pathway of BMP9 signaling is Smad1/5/8, although it can vary depending on the cell type and cellular context. BMP9 transduces signals through Smad1/5/8, as it has been described in numerous studies on endothelial cells [79,[96][97][98][99][100][101][102]. In the hepatocellular carcinoma cell line HepG2, BMP9 induces phospho-Smad1/5/8 phosphorylation leading to increased survival [103].…”
Section: Bmp9-alk1 Signalingmentioning
confidence: 83%